Az EU-csatlakozás lehetséges előnyei és hátrányai a magyar agrárgazdaságra - Tóth, László (Tér és Társadalom, 1996)
The transitions following the turn of the 1980s-1990s raised the issues about the future of Europe in a new light. The "European idea", the expansion of the EU was accompanied with the task of a possible Eastern expansion. The ideas concerning the future, however, are many times one-sided in their attitude and they are based on political and ideological notions, reflexes rather than reality. Still, they do not even meet the criteria of alternativity. The issues and problems of the future of the integration are especially serious in matters of agriculture. The agriculture of the Community has been known from the beginning as one of the most problematic fields of the integration, which, as the author of the essay sees, is the consequence of the characteristic contradiction of integration and regionalisation and which seems to be justified by all expansions/accessions so far. The future of the EU as whole and the chances of accession for those who are new applicants will largely be determined by the future of the common agricultural policy. Based on the experiences of the past 7-8 years it is evident that we have to get rid of several illusions and fears that emerged in connection with the future of the European agriculture. There is only one way to do it: Besides forecasting the possible changes of the common agricultural policy, we will have to explore the favourable and unfavourable consequences of the expected accession in order to be able to work out adequate strategies. The future and possible effects of the agrarian integration are of special importance for Hungary. The ideas outlined in the essay are meant to provide some theoretical support for the creation of the right strategies.